Penerapan Metode Participatory Experiential Learning oleh Trainer untuk Membangun dan Meningkatkan e-Loyalty Mitra Bimbel Brainy Kids - Riyan Sumarno; Tri Lestari; Siti Amriyah; Annisa Wahyu Damayanti (Politeknik Piksi Ganesha Indonesia, 2026)
Retention fluctuations of Brainy Kids partners from 52.24% (2022) to 76.81% (2024) reflect variations in digital service quality influenced by trainers. This community service aims to enhance trainer competencies to strengthen potential partner e-loyalty via improved e-service quality, e-trust, and e-satisfaction. Participatory experiential learning method was applied to 10 partner trainers over three days (December 21–23, 2025). Evaluation relied on participatory observation, daily collaborative reflection, and informal feedback from branch owners. Immediate findings reveal trainers' independent troubleshooting ability rose from 30% to 80% in simulations. Reflections and observations indicate enhanced responsiveness, confidence, and empathetic interactions. Early informal discussions with partners show positive perceptions of digital support. This program offers preliminary evidence that empowering trainers as human mediators can serve as a blueprint for human-technology integration to sustain partnerships in Indonesian non-formal education.